Thrombotic potential during pediatric acute lymphoblastic leukemia induction: Role of cell‐free DNA. Issue 5 (26th July 2021) - Kumar, Rahul; Katare, Parmeshwar B.; Lentz, Steven R.; Modi, Arunkumar J.; Sharathkumar, Anjali A.; Dayal, Sanjana
Abstract: Background: Thromboembolism affects up to 30% of children undergoing treatment for acute lymphoblastic leukemia (ALL). Increased thrombin generation has been reported in ALL, but the mechanisms remain elusive. Objective: We aimed to show that extracellular traps and cell‐free DNA (cfDNA) promote thrombin generation in pediatric ALL. Methods: In a longitudinal single‐center study, we recruited 17 consecutive pediatric ALL patients. Serial blood samples were collected at diagnosis and weekly during the 4‐week induction phase of antileukemic chemotherapy. Healthy children (n = 14) and children with deep vein thrombosis (DVT; n = 7) or sepsis (n = 5) were recruited as negative and positive controls, respectively. In plasma, we measured endogenous thrombin generation potential (ETP) and components of extracellular traps, including cfDNA. Results: In patients with ALL, ETP was increased at baseline and remained significantly elevated throughout the induction therapy. Plasma levels of cfDNA were increased at baseline and during the first 3 weeks of induction therapy. The extent of enhancement of ETP and plasma cfDNA in patients with ALL was similar to that seen in patients with DVT or sepsis. Treatment of plasma with DNase 1 lowered ETP in patients with ALL at each time point but did not affect ETP in healthy controls. Conclusion: We conclude that childhood ALL is associated with a prothrombotic milieu at the time of diagnosis that continues during induction chemotherapy, and cfDNA contributes to increased thrombogenic potential.